Health Counseling on the Importance of Complete Basic Immunization in Bontoa Village, Mandai Health Center Working Area, Maros Regency - Amina Ramadana N; Naba; Herwandi Sape; Fadhilah Rahmat; Jumiati (ITEKES Permata Ilmu Maros, 2025)
One of the problems faced in preventing diseases that can be prevented by immunization is the low coverage of complete basic immunization. The government's program in an effort to improve children's health is that before the child is one year old, basic immunization should be given completely according to a high and even schedule. In this condition, it is expected that the immune system can be formed optimally so that the impacts caused can be minimized. The purpose of this counseling activity is to increase public knowledge and awareness about the importance of complete basic immunization in preventing infectious diseases, especially Diseases That Can Be Prevented by Immunization (PD3I) so that children as the nation's successors can live healthy lives free from pain, disability and even death. The method used is lectures and discussions. This activity was carried out in the Mandai Health Center Work Area, Maros Regency with 25 participants. From the results of the counseling, there was an increase in the knowledge and understanding of mothers so that it is hoped that there will be awareness and willingness to bring their children to get immunizations according to the schedule and their age on time. This counseling activity can be carried out continuously in all Health Center work areas with government support.